2002
DOI: 10.1016/s0022-2275(20)30155-3
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of plasma noncholesterol sterols and relationship to DNA sequence polymorphism in ABCG5 and ABCG8

Abstract: The plasma concentrations of cholesterol precursor sterols and plant sterols vary over a 5-to 10-fold range among normolipidemic individuals, and provide indices of the relative rates of cholesterol synthesis and fractional absorption. In the present study, we examined the relative contributions of genetic and environmental factors to variation in the plasma concentrations and sterol-cholesterol ratios of five noncholesterol sterols, including the 5 ␣ -saturated derivative of cholesterol (cholestanol), two pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(17 citation statements)
references
References 22 publications
1
14
0
1
Order By: Relevance
“…This report details retrospective sterol analyses of stored plasma specimens of 324 male and 168 female consecutive participants (ages 22–65 years) recruited in October and November 2000. Because phytosterols are carried within lipoproteins and concentrations are correlated with total cholesterol [3, 15, 16], values were also expressed as a ratio to total cholesterol as quantified by gas chromatography–mass spectrometry (GC-MS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This report details retrospective sterol analyses of stored plasma specimens of 324 male and 168 female consecutive participants (ages 22–65 years) recruited in October and November 2000. Because phytosterols are carried within lipoproteins and concentrations are correlated with total cholesterol [3, 15, 16], values were also expressed as a ratio to total cholesterol as quantified by gas chromatography–mass spectrometry (GC-MS).…”
Section: Methodsmentioning
confidence: 99%
“…In normolipidemic individuals, circulating sitosterol concentrations vary over a five to 10-fold range [3], and this variation is highly heritable [4]. Mutations in ATP-binding cassette (ABC) half-transporter genes cause sitosterolemia, a rare autosomal recessive disorder characterized by profoundly elevated absorption and reduced biliary excretion of sitosterol [5–7].…”
Section: Introductionmentioning
confidence: 99%
“…Most samples were drawn at nonuniform times of the day, with fasting states also not accounted for, which implies that diurnal variation cannot be ruled out. However, although not specific to sitosterol, the intraindividual variation of non-cholesterol sterols has been reported to be insignificant [26], which partially alleviates limitations associated with diurnal variation. In future studies, we plan to recruit study samples over a longer timeframe, which will result in larger sample sizes without compromising the quality of the selection process, as well as obtaining complete medical records of all subjects who enroll in the study.…”
Section: Plos Onementioning
confidence: 98%
“…Genetic variants, including singlenucleotide polymorphisms (SNPs), might at least partly explain these large inter-individual variations and the wide ranges between individuals in responses to lipid-lowering medications [15]. In fact, some SNPs in intestinal cholesterol absorption genes have already been associated with fractional cholesterol absorption rates [16][17][18][19]. Additionally, several studies have reported associations between SNPs in genes related to intestinal cholesterol absorption and endogenous cholesterol synthesis with lipid-lowering effects of both pharmacological [20][21][22][23] and dietary interventions [24,25].…”
Section: Introductionmentioning
confidence: 99%